Demonstration of Feeding Vehicle‐Integrated Photovoltaic‐Converted Energy into the High‐Voltage On‐Board Network of Practical Light Commercial Vehicles for Range Extension. Issue 5 (14th November 2021) - Peibst, Robby; Fischer, Hilke; Brunner, Manuel; Schießl, Andreas; Wöhe, S.; Wecker, Reinhard; Haase, Felix; Schulte-Huxel, Henning; Blankemeyer, Susanne; Köntges, Marc; Hollemann, Christina; Brendel, Rolf; et al.
Abstract : The setting up of a practical electrically driven light commercial demonstration vehicle with integrated photovoltaics (PV) is reported. The demonstrator vehicle is equipped with 15 modules based on the crystalline Si/amorphous Si heterojunction technology. The nominal total peak power under standard testing conditions is 2180 Wp . Specifically, the PV‐converted energy is fed into the high‐voltage (HV; 400 V) board‐net for a utilization of the large capacity of the HV battery and thus for direct range extension. The demonstrator vehicle is equipped with irradiation, wind, temperature, magnetic, and global positioning system sensors. Irradiation and temperature as well as the energy flows from modules, maximum power point trackers (MPPTs), low‐voltage buffer battery to HV battery via DC/DC, and from the HV battery to the loads during an exemplarily test drive day (May 31, 2021) are monitored. The range extension obtained at this day on our test route (51° 59′ N, 9° 31′ E) was 36 km, the corresponding CO2 savings account for ≈2.3 kg. The chain efficiency of the electronic components from the input side of the MPPTs to the HV output side of the DC/DC was 68.6%, whereas the DC/DC itself has an average efficiency of 90%. Abstract : A practical electrically driven light commercial demonstration vehicle with integrated photovoltaics (PV) is set up. The PV‐converted energy is fed into the high‐voltage (400 V) board‐net. The energy flow during an exemplarily test drive day is monitored, resulting in a range extension of 36 km, a DC/DC (chain) efficiency of 90 (68.6)%, and CO2 savings of ≈2.3 kg.